metonymy Analytical deliberative approach - سليمان, بثينة (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
Pragmatics is one of the most important, newest and most active topics of modern linguistics. It has gained its characteristic from the fact that it studies the relationship of language to use in the actual conversational setting with its cultural, social, temporal and spatial components. Therefore, the purpose of the pragmatic study was to search for the intentions of the speakers in the linguistic message, those intentions that may be implicit and are not taken in the apparent literal sense, and access to them needs significant contextual evidences, which linguistics extracted when controlling the concepts of pragmatics and its foundations. The metonymy is one of the most rhetorical phenomena related to situations of communication, whether social or literary, as a rhetorical or pictorial method indicative of implicit intentions; It is interpreted by evidences of the necessary or adjacent context, and requires cooperation between the speaker and the listener. Hence, the aim of this research was to read the metonymy from a pragmatic approach.